2014
DOI: 10.1016/j.ypmed.2014.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Addressing cancer control needs of African-born immigrants in the US: A systematic literature review

Abstract: Compared to non-Hispanic Whites, African immigrants have worse cancer outcomes. However, there is little research about cancer behaviors and/or interventions in this growing population as they are generally grouped with populations from America or the Caribbean. This systematic review examines cancer-related studies that included African-born participants. We searched PsychINFO, Ovid Medline, Pubmed, CINHAL, and Web of Science for articles focusing on any type of cancer that included African-born immigrant par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 45 publications
2
29
0
Order By: Relevance
“…African‐born immigrants, one of the fastest growing immigrant groups in the United States, are a population in which the lack of culturally competent patient communication has been especially evident. In a systematic literature review of cancer care among African immigrants, Hurtado‐de‐Mendoza et al found that African immigrants have limited knowledge about cancer care, associate breast cancer with certain death, and sometimes attribute breast cancer to a punishment from God. These perceptions create barriers to screening and treatment because these patients have limited knowledge and awareness about screening practices, have emotions at odds with screening (shame, modesty, and fear of screening procedures), and have cultural values perceived to be at odds with medical practices .…”
Section: Patterns Of Care: the Second Element Of The Perfect Stormmentioning
confidence: 99%
See 1 more Smart Citation
“…African‐born immigrants, one of the fastest growing immigrant groups in the United States, are a population in which the lack of culturally competent patient communication has been especially evident. In a systematic literature review of cancer care among African immigrants, Hurtado‐de‐Mendoza et al found that African immigrants have limited knowledge about cancer care, associate breast cancer with certain death, and sometimes attribute breast cancer to a punishment from God. These perceptions create barriers to screening and treatment because these patients have limited knowledge and awareness about screening practices, have emotions at odds with screening (shame, modesty, and fear of screening procedures), and have cultural values perceived to be at odds with medical practices .…”
Section: Patterns Of Care: the Second Element Of The Perfect Stormmentioning
confidence: 99%
“…In a systematic literature review of cancer care among African immigrants, Hurtado‐de‐Mendoza et al found that African immigrants have limited knowledge about cancer care, associate breast cancer with certain death, and sometimes attribute breast cancer to a punishment from God. These perceptions create barriers to screening and treatment because these patients have limited knowledge and awareness about screening practices, have emotions at odds with screening (shame, modesty, and fear of screening procedures), and have cultural values perceived to be at odds with medical practices . Interventions that have been shown to be successful with immigrant breast cancer health are those that employ linguistically and culturally tailored programs .…”
Section: Patterns Of Care: the Second Element Of The Perfect Stormmentioning
confidence: 99%
“…There are differences between sub‐Saharan African‐born blacks and those born in the United States with respect to culture, beliefs, socioeconomic status, dietary patterns, and genetics that could affect the occurrence of cancer and other diseases . Despite these differences, cancer occurrence for blacks in the United States is typically presented in aggregate without regard to country or region of birth, thereby masking important potential differences that can inform cancer prevention and control policies and programs for African‐born black immigrants . In this article, we present what to our knowledge is for the first time the distribution of cancer incidence in sub‐Saharan African‐born blacks residing in the United States using data from the Surveillance, Epidemiology, and End Results (SEER) program.…”
Section: Introductionmentioning
confidence: 99%
“…While the role of foreign-born status has been explored in the context of BC screening among Blacks [40,41], few studies have examined the status on BC survivors’ HRQOL. Given the growing Black immigrant U.S. population [42], and the disproportionate representation of Blacks diagnosed with BC ≤ age 50 [1], understanding HRQOL in this group warrants further study.…”
Section: Discussionmentioning
confidence: 99%